A review of lactate-lactylation in malignancy: its potential in immunotherapy - Zha, Jinhui; Zhang, Junan; Lu, Jingfen; Zhang, Guangcheng; Hua, Mengzhan; Guo, Weiming; Yang, Jing; Fan, Gang (Frontiers in Immunology, 2024)
Lactic acid was formerly regarded as a byproduct of metabolism. However, extensive investigations into the intricacies of cancer development have revealed its significant contributions to tumor growth, migration, and invasion. Post-translational modifications involving lactate have been widely observed in histone and non-histone proteins, and these modifications play a crucial role in regulating gene expression by covalently attaching lactoyl groups to lysine residues in proteins. This discovery has greatly enhanced our comprehension of lactic acid's involvement in disease pathogenesis. In this article, we provide a comprehensive review of the intricate relationship between lactate and tumor immunity, the occurrence of lactylation in malignant tumors, and the exploitation of targeted lactate-lactylation in tumor immunotherapy. Additionally, we discuss future research directions, aiming to offer novel insights that could inform the investigation, diagnosis, and treatment of related diseases.